2018
DOI: 10.1371/journal.pone.0194173
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geriatric Assessment and quality of life after localized prostate cancer radiotherapy in elderly patients

Abstract: IntroductionRadiotherapy can diminish quality of life (QoL) for prostate cancer patients. Our objective was to evaluate the effect of radiotherapy on QoL in men aged 75 years or older treated with radiotherapy for a localized prostate cancer, and to identify predictors of reduced QoL.Patients and methodsWe prospectively administered a battery of geriatric (MNA, GDS, Get up and Go Test, CIRS-G, ADL, IADL, MMSE), toxicity (IPSS; IIEF 5), and QoL (QLQ C30) screening tests in 100 elderly patients before and two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 57 publications
0
17
1
2
Order By: Relevance
“…Only a minority of the population (≤3%) experienced grade ≥3 post-radiation AE in comparison with other study [ 25 ]. Older age (>70 years) was a risk factor for increased urinary toxicity in some studies; these results contrast with our work and Goineau et al study [ 26 ]. Acute and long-term gastrointestinal AE was acceptable; in literature, older age is a risk factor of digestive toxicity [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Only a minority of the population (≤3%) experienced grade ≥3 post-radiation AE in comparison with other study [ 25 ]. Older age (>70 years) was a risk factor for increased urinary toxicity in some studies; these results contrast with our work and Goineau et al study [ 26 ]. Acute and long-term gastrointestinal AE was acceptable; in literature, older age is a risk factor of digestive toxicity [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The appropriate French ethics committees approved the study (number 2014-A00300-47), and all patients gave consent for participation. A detailed description of the study methods has been published previously [29].…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding the limitations imposed by research design, many of these studies have indicated that CGA can influence care. Goineau et al [94], in a study of patients (n = 100; 75 years) with localised prostate cancer, undergoing radiotherapy treatment, found no association between CGA and QoL. However, they discovered IADL impairments at baseline in half of study participants, as well as ADL impairments in 16% of patients.…”
Section: Personalised Radiotherapy: the Role Of Frailty Assessmentmentioning
confidence: 95%